Industriestandort Deutschland droht struktureller Verlust an Wettbewerbsfähigkeit - Eric Heymann (Wirtschaftsdienst, 2022)
– The current energy crisis poses major economic growth risks for the German economy as a whole and for German industry in particular. It also represents an enormous structural challenge for Germany as an industrial nation. A comprehensive deindustrialization in Germany across all sectors is unlikely. One argument against this is the adaptability of German industry. The prospects for some industrial sectors have become significantly gloomier, however, as a result of the acute energy crisis and higher gas and energy prices in the medium term.
Keywords: O14; N60; 330; Industriestruktur; Deindustrialisierung; Internationaler Wettbewerb; Deutschland